2010
DOI: 10.1002/art.27286
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to apolipoprotein A‐I, high‐density lipoprotein, and C‐reactive protein are associated with disease activity in patients with systemic lupus erythematosus

Abstract: Objective. Inflammatory disease activity in patients with systemic lupus erythematosus (SLE) may affect the development of atherosclerosis, contributing to their increased risk of cardiovascular disease (CVD). This process may be mediated by anti-apolipoprotein A-I (anti-Apo A-I), anti-high-density lipoprotein (anti-HDL), and anti-C-reactive protein (anti-CRP) autoantibodies. We undertook this study to examine whether levels of these antibodies rise in association with increased SLE disease activity.Methods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 37 publications
4
67
1
2
Order By: Relevance
“…During the last decade, many groups have reported the presence of autoantibodies directed against PRMs and acute phase proteins in different conditions [22][23][24][25][26]. We have demonstrated associations between anti-CRP antibody levels and disease activity, histopathology as well as response to therapy in lupus patients [27,28].…”
Section: Introductionmentioning
confidence: 65%
“…During the last decade, many groups have reported the presence of autoantibodies directed against PRMs and acute phase proteins in different conditions [22][23][24][25][26]. We have demonstrated associations between anti-CRP antibody levels and disease activity, histopathology as well as response to therapy in lupus patients [27,28].…”
Section: Introductionmentioning
confidence: 65%
“…Since then, several groups have confirmed the finding of IgG class autoantibodies to CRP (anti-CRP) in SLE [12][13][14]. Analyses of antigen specificity of the anti-CRP assay used have clearly revealed that anti-CRP in SLE are directed against monomeric CRP, which is assumed to be the tissue-deposited form of the acute-phase reactant.…”
Section: Introductionmentioning
confidence: 93%
“…87 Further studies showed correlation between levels of ApoA1 antibodies and disease severity, and carotid intima-media thickness in SLE patients. [88][89][90] Recently, in a longitudinal study, Croca et al 91 also reported significant association between anti-ApoA1 IgG levels and SLE disease activity, but failed to show correlation between early anti-apoA-1 IgG positivity and morbidity, mortality, and CVD risk, which suggests about a lack of prognostic value of anti-ApoA1 antibodies for SLE-induced death or cardiovascular complications in SLE.…”
Section: Apoa1 Epitopesmentioning
confidence: 99%